Cardioprotective Effects of the Novel Compound Vastiras in a Preclinical Model of End-Organ Damage. Issue 5 (May 2020) - Altara, Raffaele; da Silva, Gustavo J.J.; Frisk, Michael; Spelta, Francesco; Zouein, Fouad A.; Louch, William E.; Booz, George W.; Cataliotti, Alessandro
Abstract : Cardiac hypertrophy and renal damage associated with hypertension are independent predictors of morbidity and mortality. In a model of hypertensive heart disease and renal damage, we tested the actions of continuous administration of Vastiras, a novel compound derived from the linear fragment of ANP (atrial natriuretic peptide), namely pro-ANP31–67, on blood pressure and associated renal and cardiac function and remodeling. Of note, this peptide, unlike the ring structured forms, does not bind to the classic natriuretic peptide receptors. Dahl/Salt–Sensitive rats fed a 4% NaCl diet for 6 weeks developed hypertension, cardiac hypertrophy, and renal damage. Four weeks of treatment with 50 to 100 ng/kg per day of Vastiras exhibited positive effects on renal function, independent of blood pressure regulation. Treated rats had increased urine excretion, natriuresis, and enhanced glomerular filtration rate. Importantly, these favorable renal effects were accompanied by improved cardiac structure and function, including attenuated cardiac hypertrophy, as indicated by decreased heart weight to body weight ratio, relative wall thickness, and left atrial diameter, as well as reduced fibrosis and normalized ratio of the diastolic mitral inflow E wave to A wave. A renal subtherapeutic dose of Vastiras (25 ng/kg per day) induced similar protective effects on the heart. At the cellular level, cardiomyocyte size and t-tubule density were preserved in Vastiras-treated compared with untreated animals. In conclusion, these data demonstrate the cardiorenal protective actions of chronic supplementation of a first-in-class compound, Vastiras, in a preclinical model of maladaptive cardiac hypertrophy and renal damage induced by hypertension. Abstract : Supplemental Digital Content is available in the text.